Emission lines properties of the radio-loud quasar LAMOST J1131+3114 - Shi, Z. X.; Comte, G.; Luo, A. L.; Zhao, Y. H.; Zhao, J. K.; Oswalt, T. D.; Wu, F. C. (Astronomy and astrophysics (Berlin), 2014)
The radio-loud quasar LAMOST J1131+3114 (Ton 580, B2 1128+315), showing asymmetrical profile in Hβ and [O III] lines, has been selected from the LAMOST Pilot Survey for further study. We present an analysis of its emission lines by means of multiple Gaussian fitting, performed on LAMOST, Apache Point Observatory, and archival spectra. The broad line region, with an Hβ line of FWHM ~ 4000 km s-1 has been fit with a double Gaussian, one of which is very broad and redshifted from the reference frame. The object is a likely Population B quasar. The [O III] λλ4959,5007 lines profiles of the source have been formally fit with two Gaussian components, one of which is as broad as ~700 km s-1. This broader component, if physically meaningful, appears to be subject to moderate velocity shock excitation. The forbidden line ratios correspond to a poorly populated area in standard diagnostic diagrams of AGN narrow line regions.